Pengaruh Aplikasi Glifosat terhadap Efikasi dan Komposisi Gulma Pertanaman Kelapa Sawit Tanaman Menghasilkan Muda - Oktavia, Kurnia; Pujisiswanto, Hidayat; Evizal, Rusdi; Susanto, Herry (Jurnal Agro Industri Perkebunan, 2019)
This study aimed to obtain the effective dose of isopropylamine glyphosate herbicide for controlling weeds in oil palm plantation andto study the change of weed composition after glyphosate application in early producing oil palm plantation.The research was conducted in smallholder oil palm plantation located in Srimulyo Kenanga Sari Village, Seputih Surabaya Sub-district, Central Lampung Regency and Weed Science Laboratory of Agriculture Faculty, Lampung University from November 2017 to January 2018. This research used randomized block design (RBD) with 4 replications and 7 treatments of 5  isopropylamine glyphosate herbicide doses (1.080, 1.440, 1.800, 2.160, and 2.520 g.ha-1), mechanical weeding, and control. The data homogeneity tested by Bartlett test, the data additivity tested by Tukey test, and the difference of median value tested by the Least Significant Difference (LSD) at 5% level. The results showed that all of isopropylamine glyphosate herbicide doses were effective in controlling total weeds, grassy weeds (Axonopus compressus, Ottochloa nodosa, Imperata cylindrica) and nutsedges (Cyperus rotundus) for 4—12 weeks after application (WAA) and broadleaf weeds (Praxelis clematidea) for 4 WAA. Glyphosate application changed weed composition at 4, 8, and 12 WAA of observations from grassy weeds to broadleaf weeds.   Keywords: composition, efficacy, herbicide, glyphosate, oil palm, weeds